2012
DOI: 10.1128/jvi.01733-12
|View full text |Cite
|
Sign up to set email alerts
|

Epitope-Specific CD8+T Cells Play a Differential Pathogenic Role in the Development of a Viral Disease Model for Multiple Sclerosis

Abstract: Theiler's virus-induced demyelinating disease has been extensively investigated as a model for persistent viral infection and multiple sclerosis (MS).؉ T cells exhibited high functional avidity for gamma interferon production, whereas VP3 173-181 -specific CD8 ؉ T cells showed low avidity. To our knowledge, this is the first report indicating that the induction of the IL-17-producing CD8 ؉ T cell type is largely epitope specific and that this specificity apparently plays a differential role in the pathogenicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 55 publications
(84 reference statements)
1
20
0
Order By: Relevance
“…In the Theiler’s virus-induced demyelinating disease model, Myoung et al recently found that CD8+ T cells specific for an epitope present in the viral capsid protein, VP3, played an unexpected causative role in initiating the chronic demyelinating phase of disease (Myoung et al, 2012). These disease-causing, virus-specific CD8+ T cells had high avidity for infected target cells and produced significant amounts of the inflammatory cytokine, IL-17 (Myoung et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Theiler’s virus-induced demyelinating disease model, Myoung et al recently found that CD8+ T cells specific for an epitope present in the viral capsid protein, VP3, played an unexpected causative role in initiating the chronic demyelinating phase of disease (Myoung et al, 2012). These disease-causing, virus-specific CD8+ T cells had high avidity for infected target cells and produced significant amounts of the inflammatory cytokine, IL-17 (Myoung et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These disease-causing, virus-specific CD8+ T cells had high avidity for infected target cells and produced significant amounts of the inflammatory cytokine, IL-17 (Myoung et al, 2012). In the same experimental system, others have found that CNS-infiltrating CD8+ T cells come into direct contact and form immunological synapses with infected neurons (McDole et al, 2010), while antiviral CD8+ T cells isolated from infected mice and then cloned in vitro can transfer an EAE-like disease when injected into naïve recipients (Libbey et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the differential expression of integrin molecules might result in the significant decrease in TNF-α-producing CD4 + T cells and IFN-γ-producing CD8 + T cells, but unaltered level of IL-17-producing CD4 + T cells compared with control mice. Thus, the significant suppression of TMEV-IDD was accompanied with the reduction of the LIs for the CD68 antigen, macrophage markers, and the reduced numbers of TNF-α-producing CD4 + cells and IFN-γ-producing CD8 + cells in the CNS of mice treated with HCA3551, because as these cell types have been implicated to play pathogenic roles in the disease development (13,34,35). These results suggest that treatment with HCA3551 decreased the number of MNCs infiltrated into the CNS of TMEV-infected mice, thereby suppressed the development of TMEV-IDD.…”
Section: Discussionmentioning
confidence: 99%
“…4B). Notably, CD4 + T cells producing TNF-α and VP3 159-166 -specific CD8 + T cells were particularly reduced among T cells in the CNS of HCA3551-treated mice, as these T cells have been associated with the pathogenesis of TMEV-IDD (34,35). The treatment design is shown in Table 1.…”
Section: Administration Of the Orally Active Small Molecule Antagonismentioning
confidence: 99%
“…Although the precise effector mechanism of the immunopathology is unknown, multiple immune components have been shown to play key roles. For example, CD4 + T helper (Th)1 cells have been associated with inflammatory demyelination, CD8 + T cells could play an effector role in axonal degeneration, and anti-viral antibody can cross react with myelin antigen (20, 23–25) (only TMEV-specific antibody can play a pathogenic role in TMEV-IDD; no other pathogenic antibodies have been reported in TMEV-IDD). This chronic TMEV-induced demyelinating disease (TMEV-IDD) resembles MS both clinically and histologically.…”
Section: Introductionmentioning
confidence: 99%